Kinematics Research of the Plunger Pump of the Gear-linked Cylinders Hydraulic Engine - Xu Wei; Zhang Hongxin; Shu Pei; Gao Lei (Jixie chuandong)
The structure and working principle of the plunger pump of the gear- linked cylinders hydraulic engine is put forward creatively for the issues that loose structure,more throttling lose,low efficiency and affected highly by working frequency that appearing in traditional plunger pump. And the structure and working principle of the gear- linked cylinders hydraulic engine are expounded. The plunger pump of the gear- linked cylinders hydraulic engine is a kind of liner reciprocating plunger pump that direct convert the indicated work into fluid pressure,it has advantages of compact structure and high volumetric efficiency. The kinematics research of the plunger pump of the gear- linked cylinders hydraulic engine provides reference for the later dynamics analysis,flow stress analysis,cam slot line optimization and prototype trial.